Assessing sales loss from automobile recalls: a Toyota case study. (1st January 2014) - Shin, Heechang; Richardson, Robert; Soluade, Oredola
Automobile companies recall vehicles whenever they are perceived to have defects that affect safety. Since market responses to a product recall may be different depending on the size of cars in the recall, the analysis separated the recalls into major events with more than 500, 000 cars per recall, and minor recalls with less than 500, 000 cars per recall. In this paper, the impact on sales was measured in order to understand the customer's reaction under these circumstances. The well-publicised recalls in November 2009 and January 2010 are the focus of this study. The paper also investigates the impact of the recalls on the Japanese auto industry, as well as stock market performance of Toyota. The conclusion from the model indicates that major recalls have a negative impact on the market share with a three-month lag, while minor recalls showed a positive impact on the market share after four months. However, its impact on the stock market performance is immediate and shows no evidence of lagging effect for stock prices. Analysis on Japanese auto industry identifies that the market share trajectories of Honda and Toyota shows similar patterns which suggests that consumer perceptions of these companies are similar.